A Comparative Study of The Indonesian and English Articles - FX. Nadar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1996)
Commonwealth Department of Education in Australia (1983:22) has concluded that articles will be an area of difficulty for Indonesian students. This is because the